Nefropatía asociada a VIH. Reporte de un caso. - BRAVO ZÚÑIGA, Jessica; CIEZA ZEVALLOS, Javier; FERRUFINO LLACH, Juan (Revista Médica Herediana, 2013)
HIV associated nephropathy can present as heavy proteinuria or advanced renal insufficiency leading to dialysis dependent renal failure. We report the clinical and histopathological outcome in one patient when HIV disease manifested as HIV nephropathy. A 31 years black male developed progressive renal failure within six weeks serum creatinine increased from 1.2 mg/dl to 3.17 mg/dl. Evaluation revealed HIV antibody positive with CD4 251/ul and nephrotic proteinuria. Renal biopsy showed collapsing glomerulopathy and microcystic dilatation of tubules. The clinical presentation, physiopatology and probable treatment are discussed.